2021
DOI: 10.54472/jobig.1034612
|View full text |Cite
|
Sign up to set email alerts
|

Di̇ji̇tal İndi̇ri̇m Kuponlarina Dai̇r Müşteri̇ Algisi Ve Davranişi Üzeri̇ne Bi̇r Araştirma

Abstract: Digital coupons, generally considered as a marketing strategy to increase sales and customer loyalty, are important elements in the observation of customer attitudes and perceptions. The main question in the literature is whether these coupons should be redeemed or not, and their effectiveness is discussed depending on their use. However, even if digital coupons are not redeemed after they are acquired in online environments, the way they are obtained or perceived can provide marketers with information about c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, many studies suggest that the number of e-coupons that are finally used and redeemed by consumers is not as high as expected, given the proportion of retailers that issued e-coupons [6][7][8][9]. Thus, it is important for marketers to identify and analyze e-coupon redemption to develop effective marketing strategies [10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, many studies suggest that the number of e-coupons that are finally used and redeemed by consumers is not as high as expected, given the proportion of retailers that issued e-coupons [6][7][8][9]. Thus, it is important for marketers to identify and analyze e-coupon redemption to develop effective marketing strategies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous coupon redemption studies highlight the importance of consumer demographic characteristics in explaining consumers' coupon-using behaviors, which helps to achieve the best results in digital marketing [10][11][12][13]. A 2021 survey about couponing in the United States found that more women than men reported always using coupon aggregators while shopping online, with 14% of female respondents always using them, while only 8% of men said the same.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations